The changing face of oyster culture in New South Wales, Australia - O'Connor, W A; Dove, M C (Journal of Shellfish Research, 2009)
Oyster farming is one of the oldest aquaculture industries in Australia and, in New South Wales (NSW), its history dates back some 130 y. Like other industries, it has evolved over time, but during the past 5 y, a number of significant changes have occurred. Although Sydney rock oysters (Saccostrea glomerata [SRO]) remain the most important commercial species, the culture of Pacific oysters (Crassostrea gigas), particularly triploids, has increased significantly. Interest in cultivating other commercially important species, such as flat oysters, Ostrea angasi, has also increased. Overall, hatchery-produced oyster seed has become more readily accessible, particularly for S. glomerata, which, prior to 2003, had been largely unavailable to the majority of the rock oyster industry. For both S. glomerata and C. gigas, breeding programs have become an integral part of industry development and have been the primary reason for hatchery seed uptake in NSW. Across the oyster industry, the emphasis placed on the importance of demonstrating environmental sustainability has increased, and both industry and government have been proactive in protecting the estuarine environments in which oyster farming occurs. Collectively, hatchery development, oyster breeding, and environmental research has "spawned" a number of new research initiatives that have increased fundamental oyster research during the past 5 y.